Interaction of Half Oxa-/Half cis-Platin Complex with Human Superoxide Dismutase and Induced Reduction of Neurotoxicity - Cantini, Francesca (ACS Med Chem Lett, 2018)
[Image: see text] The formation of amorphous protein aggregates containing human superoxide dismutase (hSOD1) is thought to be involved in amyotrophic lateral sclerosis onset. cis-Platin inhibits the oligomerization of apo hSOD1, but its toxicity precludes any possible use in therapy. Herein, we propose a less toxic platinum complex, namely oxa/cis-platin, as hSOD1 antiaggregation lead compound. Oxa/cis-platin is able to interact with hSOD1 in the disulfide oxidized apo form by binding cysteine 111 (Cys111). The mild neurotoxic phenomena induced in vitro and in vivo by oxa/cis-platin can be successfully reverted by using lypoyl derivatives, which do not interfere with the antiaggregation properties of the platin derivative.